Investigation of biomarker properties of DARS2 to distinguish squamous cell carcinoma from keratoacanthoma - Üçer, Özlem; Kocaman, Nevin (My University, 2022)
Aim: This study was aimed at investigating the effectiveness of DARS2 protein expression in the differential diagnosis of squamous cell carcinoma (SCC) and keratoacanthoma (KA). Materials and Methods: A total of 60 cases, 30 SCC and 30 KA, diagnosed in the Fırat University, Faculty of Medicine, Department of Pathology, were analysed immuno- histochemically by studying the DARS2 protein. Results: DARS2 expression values were found to be statistically significant in the differ- ential diagnosis of SCC and KA (p<0.05). Conclusion: The marker used in this study was found useful in the differential diagnosis of SCC and KA, and it is recommended that, further molecular and genetic studies be carried out, this will facilitate the accurate diagnosis of SCC from KA.
Keywords: Dermatoloji; Patoloji; Onkoloji